2016
DOI: 10.1002/qua.25283
|View full text |Cite
|
Sign up to set email alerts
|

Counter anion in Li+‐encapsulated C60 can further enhance the rate of Diels–Alder reaction: A DFT study

Abstract: Density functional theory calculations were carried out to investigate the Diels–Alder cycloaddition between cyclopentadiene and C60 after the encapsulation of Li+ ion with transition states identified and confirmed by intrinsic reaction coordinate calculations. Our results showed that the Li+‐encapsulation results in a lower energy barrier and the presence of counter anion PF6− can further reduce the energy barrier, making the trend in agreement with the experimental results. In addition, the influencing fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…From then on, various kinds of FTMC have been prepared and structurally characterized. , An interesting characteristic for such an FTMC is that it can encage atoms, ions, and small molecules to form endohedral complexes, which is named endohedral metallofullerenes, because the metal atoms are encapsulated within a hollow carbon cage. Since then, many other experimental and computational works in such fields concerning cation-/anion-encapsulated fullerene chemistry have been greatly achieved. Recently, Tobita and co-workers reported the preparations and structural characterizations of the intriguing FTMC, that is, iridium and platinum complexes of the lithium-cation-encapsulated fullerene Li + @C 60 …”
Section: Introductionmentioning
confidence: 99%
“…From then on, various kinds of FTMC have been prepared and structurally characterized. , An interesting characteristic for such an FTMC is that it can encage atoms, ions, and small molecules to form endohedral complexes, which is named endohedral metallofullerenes, because the metal atoms are encapsulated within a hollow carbon cage. Since then, many other experimental and computational works in such fields concerning cation-/anion-encapsulated fullerene chemistry have been greatly achieved. Recently, Tobita and co-workers reported the preparations and structural characterizations of the intriguing FTMC, that is, iridium and platinum complexes of the lithium-cation-encapsulated fullerene Li + @C 60 …”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [43] investigated the effect of counter anion in Li + -encapsulated C 60 during the DA reaction. Cui et al [44] showed the thermodynamic feasibility of cycloaddition reactions between CpH and Ca 2+ @C 60 as well as M + @C 60 (M = Li, Na, K, Rb, and Cs).…”
Section: Introductionmentioning
confidence: 99%